Holocene Climatic Changes in the Negev Desert (Israel): Pollen and Stable Isotopes (13C/12C and 15N/14N) Records from Atzmaut and Ramon I Zoogenic Deposits - Anna Babenko (Quaternary)
Two zoogenic deposits from the central part of the Negev Desert (Israel) were investigated by stable isotopes (carbon 13C/12C and nitrogen 15N/14N) and pollen analyses. The merger of these data and results of radiocarbon dating of Atzmaut and Ramon I deposits enabled us to reconstruct climate and vegetation changes in the Negev Desert over the past 8500 years. Decrease of the δ13C value in plant remains is a sensitive indicator of paleoclimatic conditions in the region. The decline of the δ13C value over the past 8500 years almost fully coincides with an increase of the total pollen concentration, the proportion of Poaceae pollen in the profile of zoogenic deposits and wetter periods. Thus, four humid periods are identified, from the middle of the 4th millennium to the end of 3rd millennium BC, the 1st half of the 2nd millennium BC, from the 2nd half of the 1st millennium BC to the 1st half of the 1st millennium AD and the middle of the 2nd millennium AD. The δ15N value of plant remains is a less sensitive indicator of climate dynamics and represents the most significant change of precipitation in the region by the end of the 3rd millennium BC.